INTEGRASI PENDEKATAN SISTEM DAN MANAJEMEN BERBASIS PROSES: TRANSFORMASI BIROKRASI MENUJU MUTU TERPADU DALAM INSTITUSI PENDIDIKAN - Hafid Murgantara; Kasmal; Anis Widayati; Azainil; Laili Komariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to comprehensively examine the implementation of an open systems approach and process-based management in transforming educational bureaucracy toward sustainable quality improvement. The background of this research is rooted in the condition of education management in Indonesia, which remains partial, poorly integrated, bureaucratic, and less adaptive to dynamic changes. This study employs a qualitative descriptive approach using literature analysis and conceptual review of Total Quality Management (TQM), systems theory, and educational bureaucratic reform. The findings indicate that the open systems approach enables educational institutions to interact dynamically with their environment through integrated mechanisms of input, process, output, and feedback. The implementation of process-based management using tools such as SIPOC and the PDCA cycle has been shown to improve operational efficiency, reduce organizational fragmentation, and strengthen data-driven decision-making. Furthermore, the transformation of bureaucracy from a traditional model to an organic-adaptive model is a key factor in fostering innovative, collaborative, and responsive educational organizations that meet stakeholders’ needs. This systemic integration is further reinforced by the application of quality assurance standards such as Internal Quality Assurance Systems (SPMI) and ISO 9001:2015, which ensure consistency in educational service quality. Therefore, this study confirms that integrating an open systems approach with process-based management is an effective strategy for reforming educational bureaucracy and enhancing service quality in a sustainable manner.